Photophysical, photochemical and aggregation behavior of novel peripherally tetra-substituted phthalocyanine derivatives - Saka, Ece Tugba; Gol, Cem; Durmuş, Mahmut; Kantekin, Halit; Biyikhoglu, Zekeriya (Elsevier Science Sa, 2012)
In this study, the novel metal-free (4) and zinc (II) (5) phthalocyanine compounds substituted with four 1-(2-oxyethyl)-4-piperidone ethylene ketal functional groups at peripheral positions have been prepared. These new phthalocyanine compounds have been characterized by IR, H-1 NMR, C-13 NMR spectroscopy, MS spectral data and elemental analysis. The synthesized phthalocyanine compounds exhibited excellent solubility in common organic solvents and the zinc (II) phthalocyanine complex (5) showed J-type aggregation in chloroform. The photophysical and photochemical properties of metal-free (4) and zinc (II) (5) phthalocyanine complexes were also investigated in DMSO. The investigation of the photophysical and photochemical properties of photosensitizers is very useful for photodynamic therapy (PDT) applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Zinc; J-aggregation; Photophysical; Photochemical; Singlet oxygen